2017
DOI: 10.2134/jeq2017.07.0258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the APEX Model to Simulate Runoff Quality from Agricultural Fields in the Southern Region of the United States

Abstract: The Agricultural Policy Environmental eXtender (APEX) model has been widely applied to assess phosphorus (P) loss in runoff water and has been proposed as a model to support practical decisions regarding agricultural P management, as well as a model to evaluate tools such as the P Index. The aim of this study is to evaluate the performance of APEX to simulate P losses from agricultural systems to determine its potential use for refinement or replacement of the P Index in the southern region of the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The data contained in PLEAD have been used by several research groups in multiple research studies to address important modeling questions relevant to P management planning. In the US southern region, Ramirez‐Avila et al (2017) found that when calibrated, APEX satisfactorily predicted event‐based surface runoff volumes for most sites but did not adequately predict sediment, dissolved P, or total P losses in runoff water. Specifically, they found that the APEX model tended to underestimate dissolved and total P losses from fields where manure was surface applied and attributed this to the need of a surface manure P pool routine in the model.…”
Section: Potential Uses Of Databasementioning
confidence: 96%
“…The data contained in PLEAD have been used by several research groups in multiple research studies to address important modeling questions relevant to P management planning. In the US southern region, Ramirez‐Avila et al (2017) found that when calibrated, APEX satisfactorily predicted event‐based surface runoff volumes for most sites but did not adequately predict sediment, dissolved P, or total P losses in runoff water. Specifically, they found that the APEX model tended to underestimate dissolved and total P losses from fields where manure was surface applied and attributed this to the need of a surface manure P pool routine in the model.…”
Section: Potential Uses Of Databasementioning
confidence: 96%
“…Model input data and measured dissolved and total P loads were obtained from the P Loss in runoff Events from Agricultural fields Database (PLEAD; Bolster et al, 2019). Details of the field sites and experimental conditions are described in Bolster et al (2019) and Ramirez et al (2017). Briefly, two subwatersheds (11.2 and 13 ha in…”
Section: Example Usementioning
confidence: 99%
“…Additionally, at these finer scales, key natural system processes and interactions might be better understood, reducing the number of uncertainties that the model needs to capture, but the impact of precision error around each uncertainty in the model or the input data is enhanced (Refsgaard et al, 2007). Accordingly, Baffaut et al (2017), Bhandari et al (2017), Bolster et al (2017), Forsberg et al (2017), Nelson et al (2017), and Ramirez‐Avila et al (2017) report that fate‐and‐transport models can perform well when applied in locations where they have been carefully calibrated and corroborated, but they perform poorly for P and sediment when applied in locations where they have not been adequately calibrated or corroborated. Elsewhere, Bhandari et al (2017) and Ramirez‐Avila et al (2017) find that calibrated versions of APEX perform better in predicting total P losses than uncalibrated versions of APEX.…”
Section: Phosphorus Site Assessment and Water Qualitymentioning
confidence: 99%
“…Accordingly, Baffaut et al (2017), Bhandari et al (2017), Bolster et al (2017), Forsberg et al (2017), Nelson et al (2017), and Ramirez‐Avila et al (2017) report that fate‐and‐transport models can perform well when applied in locations where they have been carefully calibrated and corroborated, but they perform poorly for P and sediment when applied in locations where they have not been adequately calibrated or corroborated. Elsewhere, Bhandari et al (2017) and Ramirez‐Avila et al (2017) find that calibrated versions of APEX perform better in predicting total P losses than uncalibrated versions of APEX. Nelson et al (2017) seeks to develop regional parameters to enable the widespread transfer of APEX to different sites.…”
Section: Phosphorus Site Assessment and Water Qualitymentioning
confidence: 99%